Structural Basis for the Modulation of CDK-Dependent/Independent Activity of Cyclin D1 - Ferrer, Jean-Luc (2006)
D-type cyclins are key regulators of the cell division cycle. In association with Cyclin Dependent Kinases (CDK) 2/4/6, they control the G(1)/S-phase transition in part by phosphorylation and inactivation of tumor suppressor of retinoblastoma family. Defective regulation of the G(1)/S transition is a well-known cause of cancer, making the cyclin D1-CDK4/6 complex a promising therapeutic target. Our objective is to develop inhibitors that would block the formation or the activation of the cyclin D1-CDK4/6 complex, using in silico docking experiments on a structural homology model of the cyclin D1-CDK4/6 complex. To this end we focused on the cyclin subunit in three different ways: (1) targeting the part of the cyclin D1 facing the N-terminal domain of CDK4/6, in order to prevent the dimer formation; (2) targeting the part of the cyclin D1 facing the C-terminal domain of CDK4/6, in order to prevent the activation of CDK4/6 by blocking the T-loop in an inactive conformation, and also to destabilize the dimer; (3) targeting the groove of cyclin D1 where p21 binds, in order to mimic its inhibition mode by preventing binding of cyclin D1-CDK4/6 complex to its targets. Our strategy, and the tools we developed, will provide a computational basis to design lead compounds for novel cancer therapeutics, targeting a broad range of proteins involved in the regulation of the cell cycle.